Nilai Perusahaan LQ45 Periode 2015-2018: Return On Asset (ROA), Corporate Social Responsibility (CSR), dan Kepemilikan Manajerial - Atsari Sujud; Mila Ayu Novitasari (Oikonomia: Jurnal Manajemen, 2023)
Purpose This study aims to analyze the effect of Return On Assets (ROA), Corporate Social Responsibility (CSR), and managerial ownership on company value in LQ45 index companies listed on the Indonesia Stock Exchange (IDX) in 2015-2018. Methodology This study used multiple linear analysis methods with the help of the SPSS version 23 program. The number of samples obtained from the purposive sampling technique in this study were 11 LQ45 index companies. Findings The results of the study show that manager ownership provides the greatest contribution in influencing firm value. After that proceed with ROA. While CSR is not significant in influencing the value of the company. Suggestions Companies need to pay attention to changes in ROA and especially the ownership of managers in their efforts to influence company value.